Prosedur Pelaksanaan Program Kemitraan dan Bina Lingkungan (PKBL) Pada PT. Pelabuhan Indonesia Regional 1 Cabang Kuala Tanjung Tahun 2022 - Yahratun Usnan Nisa BR Pasaribu; Arnida Wahyuni Lubis (Jurnal Riset Ekonomi dan Akuntansi, 2023)
Community development programs and partnerships. The Partnership Program was created to help small businesses grow and become independent. Qualitative descriptive research methodology was used for this investigation. This approach seeks to present a fairly clear picture of the problem under study. To conduct this investigation rigorously, PT. Pelindo Regional Kuala Tanjung Branch was assigned by the Partnership and Community Development Program (PKBL). Therefore, the researchers who wrote this report collected data on the value of receivables as of December 31, 2022. To make it easier for companies to understand the prospects of their partners, the company categorizes its partners in the payment of receivables. The four associate positions included in the classification are Current, Substandard, Doubtful, and Stuck. PT Pelabuhan Indoneisa Regional 1 (Persero) Kuala Tanjung Branch in the period of December 31, 2022 provided loans to partners from various sectors with a total of 92 partners. The total remaining receivables in the current partner classification amounted to IDR 10,729,776,409.00,-, in the non-current partner classification amounted to IDR 5,589,839,653.00,- ,in the doubtful partner classification amounted to IDR 791,912,104.00,- and the total remaining receivables in the current partner classification amounted to IDR 5,085,536,468.00,-. As we can see, the total remaining receivables between the current and current partner classifications are not too far apart like the substandard and doubtful partner classifications.